2021
DOI: 10.2147/vhrm.s306540
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Cancer Effect of Pitavastatin May Be a Drug-Specific Effect: Subgroup Analysis of the TOHO-LIP Study

Abstract: The significance of statin treatment for the reduction of cardiovascular (CV) disease has been reported, whereas other reports have also described anti-cancer properties associated with the class effect of statins. However, the differences in anti-cancer effect of various types of statins have rarely been examined. Pitavastatin is a statin with a different chemical structure and pharmacokinetics from other statins, and the mechanism of the specific anti-cancer effect of pitavastatin has been reported in in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Pitavastatin was chosen rather than other statins due to its lipophilic nature, which enables its availability in extrahepatic tissues, and because its half-life is longer, which allows for the continuous inhibition of the targeted receptor (HMGCR) ( Catapano, 2010 , Barbalata et al, 2020 ). Pitavastatin has shown superiority over atorvastatin in preventing carcinogenesis ( Nagayama et al, 2021 ). In addition, although much higher doses of statins are usually needed to produce antitumor activities, hypercholesterolemia doses of both cerivastatin and pitavastatin can produce anti-cancer activity ( Jiang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pitavastatin was chosen rather than other statins due to its lipophilic nature, which enables its availability in extrahepatic tissues, and because its half-life is longer, which allows for the continuous inhibition of the targeted receptor (HMGCR) ( Catapano, 2010 , Barbalata et al, 2020 ). Pitavastatin has shown superiority over atorvastatin in preventing carcinogenesis ( Nagayama et al, 2021 ). In addition, although much higher doses of statins are usually needed to produce antitumor activities, hypercholesterolemia doses of both cerivastatin and pitavastatin can produce anti-cancer activity ( Jiang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although statins may have additive or synergistic effects with standard chemotherapy protocols ( Stryjkowska-Góra et al, 2015 ), its efficacy in combination with neoadjuvant regimens in patients with breast cancer has not yet been evaluated. Consequently, it is worthwhile to study whether statins can potentiate the tumor response of neoadjuvant breast cancer therapy, especially pitavastatin, which has shown superiority in reducing the incidence of cancer cases in comparison to atorvastatin ( Nagayama et al, 2021 ). This study aimed to evaluate the efficacy of pitavastatin as an adjuvant therapy added to neoadjuvant breast cancer therapy in patients with breast cancer in comparison to breast cancer patients who received only the neoadjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Otahal and his team proved that fluvastatin or pitavastatin combined with erlotinib led to apoptosis in human lung adenocarcinoma cells with a mutated or overexpressed epidermal growth factor receptor (EGFR) [38][39][40]. In cancer studies, it has been shown that statin use can significantly reduce mortality in women [41].…”
Section: Cholesterol Biosynthesis Statin Structure and Their Applicat...mentioning
confidence: 99%
“…Today, PITA has been found to be related to a reduction in the risk of cancer recurrence and mortality, and in combination with chemotherapeutic drugs, it has been found to be effective in overcoming resistance in resistant tumor cells. Therefore, there has been increased interest in PITA as a potential therapeutic agent for use in anti‐cancer therapy (Nagayama et al, 2021). Among the statins, PITA shows the strongest effect in reducing the viability of cancer cells in breast cancer and glioblastoma (Tilija Pun et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there has been increased interest in PITA as a potential therapeutic agent for use in anti-cancer therapy (Nagayama et al, 2021). Among the statins, PITA shows the strongest effect in reducing the viability of cancer cells in breast cancer and glioblastoma (Tilija Pun et al, 2022).…”
mentioning
confidence: 99%